First records of Nausigaster flukei (Diptera: Syrphidae) from Argentina - Mengual, Ximo (2015)
Nausigaster flukei Curran is recorded for the first time from Argentina. New specimens were collected in Mendoza, Jujuy and La Rioja provinces (Argentina), in the Monte and Chaco Phytogeographical Provinces. New records broaden the distribution of this species previously known from Paraguay and south Brazil and represent the first record of the genus Nausigaster from Argentina since 1892.